Carbon loss and chemical changes from permafrost collapse in the northern Tibetan Plateau. Issue 7 (5th July 2016) - Mu, Cuicui; Zhang, Tingjun; Zhang, Xiankai; Li, Lili; Guo, Hong; Zhao, Qian; Cao, Lin; Wu, Qingbai; Cheng, Guodong
Abstract: Permafrost collapse, known as thermokarst, can alter soil properties and carbon emissions. However, little is known regarding the effects of permafrost collapse in upland landscapes on the biogeochemical processes that affect carbon balance. In this study, we measured soil carbon and physiochemical properties at a large thermokarst feature on a hillslope in the northeastern Tibetan Plateau. We categorized surfaces into three different microrelief patches based on type and extent of collapse (control, drape, and exposed areas). Permafrost collapse resulted in substantial decreases of surface soil carbon and nitrogen stocks, with losses of 29.6 ± 4.2% and 28.9 ± 3.1% for carbon and nitrogen, respectively, in the 0–10 cm soil layer. Laboratory incubation experiments indicated that control soil had significantly higher CO2 production rates than that of drapes. The results from Fourier transform infrared spectroscopy analysis showed that exposed soils accumulated some organic matter due to their low position within the feature, which was accompanied by substantial changes in the chemical structure and characteristics of the soil carbon. Exposed soils had higher hydrocarbon and lignin/phenol backbone content than in control and drape soils in the 0–10 cm layer. This study demonstrates that permafrost collapse can cause abundant carbon and nitrogen loss, potentially from mineralization, leaching, photodegradation, and lateral displacement. These results demonstrate that permafrost collapse redistributes the soil organic matter, changes its chemical characteristics, and leads to losses of organic carbon due to the greenhouse gas emission. Key Points: Permafrost collapse causes soil carbon and nitrogen loss, especially in the 10 cm soil surface layer Permafrost collapse affects soil organic matter fractions and consequently CO2 production rates